The role of CBL family ubiquitin ligases in cancer progression and therapeutic strategies - Ren, Jiaqi; Lv, Linlin; Tao, Xufeng; Zhai, Xiaohan; Chen, Xuyang; Yu, Hao; Zhao, Xinya; Kong, Xin; Yu, Zhan; Dong, Deshi; Liu, Jing (Frontiers in Pharmacology, 2024)
The CBL (Casitas B-lineage lymphoma) family, as a class of ubiquitin ligases, can regulate signal transduction and activate receptor tyrosine kinases through various tyrosine kinase-dependent pathways. There are three members of the family : c-CBL, CBL-b, and CBL-c. Numerous studies have demonstrated the important role of CBL in various cellular pathways, particularly those involved in the occurrence and progression of cancer, hematopoietic development, and regulation of T cell receptors. Therefore, the purpose of this review is to comprehensively summarize the function and regulatory role of CBL family proteins in different human tumors, as well as the progress of drug research targeting CBL family, so as to provide a broader clinical measurement strategy for the treatment of tumors.